Renewable and sustainable bioenergy production from microalgal co-cultivation with palm oil mill effluent (POME): A review - Ahmad, A. (Elsevier Ltd, 2016)
Sustainable and cost effective ways to produce renewable energy from biomass have generated considerable interest. Palm oil industries generates huge amount of waste. From one tonne of processed fresh fruit bunches (FFB), different types of wastes are generated which includes empty fruit bunch (EFB) (23), mesocarp fiber (12), shell (5) and palm oil mill effluent (POME) (60). POME has a high chemical and biochemical oxygen demand and mineral content such as nitrogen and phosphorous which can cause severe pollution to the environment. This can be a great nutrient for algal cultivation whilst remediating effluent and generating biomethane through anaerobic digestion. Algae capable of producing lipids and hydrocarbons with their photosynthetic abilities are among potential candidates for bioenergy generation. The harvested microalgal biomass can be used to produce bioethanol through fermentation. An integrated wastewater treatment and renewable bioenergy production would be an added benefit to the oil palm industry. This review discusses several potential strategies for tackling the environmental problems generated by POME together with renewable energies production, such as biomethane and biohydrogen. In addition, the prospects and technologies for commercialization of those renewable energies are discussed in detail. Apart from that, co-cultivation of microalgae using POME for biodiesel, bioethanol and biomethane production together with wastewater treatments are suggested as a new process for the enhancement renewable energies generation from oil palm mills. This unrealistic approach will ultimately become an essential standard reference for scientists, oil palm millers and government stakeholders. Â© 2016 Elsevier Ltd